Contrast induced acute hypersensitivity reaction in a 10-year-old patient: A rare case study. (August 2022) - Fatima, Nabeela; Badar, Juveria; Khatoon, Fatima
Abstract: Background: Immediate skin rashes, flushing, or urticarial pruritus, rhinorrhea, nausea, short retching, and/or vomiting, diaphoresis, coughing, and vertigo are all symptoms of mild hypersensitivity reactions with an incidence of 3%. Case presentation: A 10-year old male child presented with acute hypersensitivity reaction due to the contrast used during the CECT scan. Discussion: Contrast should always be used in caution with children. Although most of them are acute and resolve with minimal treatment but few of these reactions may lead to fatalities. Conclusion: Recognizing the type of contrast reaction is crucial to treating it. Rapid recognition of the signs and symptoms of a contrast response allows radiology personnel to quickly determine the type of reaction, allowing for faster treatment and reversal. Highlights: Here, we presemt a case of 10 year old kid who developed severe hypersensitivity after giving IV contrast. Use of contrast in children should be indicated with utmost precaution. For children requiring contrast induced scans, best approach is to hospitalize them and carry on the scans.